2001
DOI: 10.1891/1061-3749.9.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the California Critical Thinking Tests

Abstract: The evaluation of critical thinking, as with any other measure, must employ instruments that meet appropriate psychometric standards. Therefore, the purpose of this study was to investigate the psychometricproperties of the two California Critical Thinking Tests. Two samples of undergraduate students enrolled in a southern comprehensive university took the California Critical Thinking Skills Test (TST) and the California Critical Thinking Dispositions Inventory (TDI). A portion of the participants, who were nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…Because of validity and other concerns expressed by researchers about the CCTDI (Bondy, Koenigseder, Ishee, & Williams, 2001;Walsh & Hardy, 1997), the UF-EMI was developed as a more domain-specific measure of critical thinking dispositions (Ricketts & Rudd, 2005). The UF-EMI focuses on three subscales or constructs: innovativeness, cognitive maturity, and engagement.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Because of validity and other concerns expressed by researchers about the CCTDI (Bondy, Koenigseder, Ishee, & Williams, 2001;Walsh & Hardy, 1997), the UF-EMI was developed as a more domain-specific measure of critical thinking dispositions (Ricketts & Rudd, 2005). The UF-EMI focuses on three subscales or constructs: innovativeness, cognitive maturity, and engagement.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…The CCTST is based on the Delphi Expert Consensus definition of critical thinking (Bondy, Koenigseder, Ishee, & Williams, 2001;Facione, 1990;Stone et al, 2001). The CCTST provides six scores: five subscales and an overall critical thinking score (Bondy et al, 2001;Stone et al, 2001).…”
Section: The California Critical Thinking Skills Test the Californiamentioning
confidence: 99%
“…Thinking Disposition Inventory (CCTDI) is designed to measure the affective, attitudinal dimension of critical thinking (Bondy et al, 2001;Stone et al, 2001). It is often used in conjunction with the CCTST.…”
Section: The California Critical Thinking Disposition Inventory the mentioning
confidence: 99%
See 1 more Smart Citation
“…There were 215 hits in ProQuest with 129 being peered reviewed. These inventories ranged from the California Critical Thinking Disposition Inventory, who reported psychometrics on this instrument, and found that it did not have sufficient psychometric properties to assess individual abilities nor sufficient stability reliability (Bondy, Koenigseder, Ishee, & Williams, 2001) to colleges, like the Southern Illinois University College of Education Edwardsville, that require every student that applies to the college to take the Student Disposition Inventory. Although the psychometrics for this inventory were not reported, The Texas San Antonio Future Disposition Inventory did report a rho <.08 on all of the subscales and significant discriminate validity that differentiated between known groups (Osman, Gutierrez, Barrios, Wong, Freedenthal & Lozano, 2010).…”
Section: Sustainability Instrumentsmentioning
confidence: 99%